A brief review on activated carbon derived from agriculture by-product - Yahya M.A.; Mansor M.H.; Zolkarnaini W.A.A.W.; Rusli N.S.; Aminuddin A.; Mohamad K.; Sabhan F.A.M.; Atik A.A.A.; Ozair L.N. (American Institute of Physics Inc., 2024)
Indexed by WOS/ Scopus